Influence of pretension on mechanical properties of carbon fiber in the filament winding process - GENÇ, GARİP; AKKUŞ, NİHAT (SPRINGER LONDON LTD, 2017)
The present study has investigated the effect of the roving tension (pretension force) on the strength of continuous carbon fiber used in the Filament Winding (FW) process. Pretension force is generally applied to composite products manufactured by FW technology to lay out the carbon fiber onto the cylindrical tube in a correct way. However, a considerable amount of damage occurs in the fibers during fiber movement trough pulleys in the pretension unit. A winding system was designed to simulate the process to understand the effects of the parameters such as roving tension, pulley diameter, and contact angle between pulley and fiber. Several experimental tests have been performed by changing pulley diameters and tension forces to understand the effect of these parameters. According to these experiments, the angle between the pulley and the amount of force applied to the carbon fiber generate the damage on the carbon fiber. Tension tests were also conducted to evaluate the strength of the damaged and undamaged carbon fiber. Experimental results indicate that the tensile strength of carbon fiber is reduced by 10 to 43% because of a change to the roving tension (pretensioning) parameters.
Keywords: Carbon fiber; Mechanical properties; Filament winding; Roving tension; Strength loss; CONTROL-SYSTEM DESIGN; FULL SECTION PARTS; PRESSURE-VESSELS; PROCESS MODEL; CYLINDERS; TENSION; PARAMETERS; STRENGTH; FAILURE